Ectoenzymatic activity and glucose heterotrophic metabolism in a shallow estuary (Ria de Aveiro, Portugal): influence of bed sediments and salt marshes - Cunha, M. A.
Bacterioplankton abundance and activity were studied in the estuarine system of Ria de Aveiro (Portugal) to test if tidal resuspension of sediments and transport of particles from the salt marshes may act as factors of variability of bacterial communities. The total and attached cell abundance, ectoenzymatic activity and the heterotrophic metabolism of glucose, as well as seston, chlorophyll a and particulate organic carbon (POC) were monitored during four 10-h periods along the tidal cycle at four sampling sites across a transect. The variation of particulate materials (seston, POC and chlorophyll a ) along the transect was not significantly correlated with either distance to the margin or distance to the sediment surface. Nevertheless, proximity to the salt marsh or to the bottom sediment surface favoured glucose incorporation and aminopeptidase activity. A multiple stepwise linear regression analysis using temperature, salinity, seston, POC, chlorophyll a , distance to sediment surface and distance to the margin as independent variables explained 66.5% of the variability of the fraction of particle-attached bacteria and only a very small proportion (12–43%) of the observed variability of total bacterial abundance, ectoenzymatic activity and glucose utilization. The spatial patterns of variation of the concentration of particulate material (seston, POC and chlorophyll a ) do not clearly indicate the occurrence of sediment resuspension and runoff from the margins. This, together with the poor contribution of these parameters to the transversal and tidal variability of bacterial activity, dismisses the importance of inputs of suspended material across the sediment/water interface and from neighbouring salt marshes in the control of bacterial density and activity.